An analysis of crack evolution of a 12Cr13 stainless steel during forging process. (October 2015) - Guo, Wei-min; Xu, Na; Ding, Ning; Shi, Jun-bo; Wu, C.M. Lawrence
Highlights: Report on crack formation in a forging steel plate. The crack surface was analyzed by using SEM. Optical microstructure was analyzed by using optical microscopy. EPMA was used to detect phosphors existence. Abstract: The analysis of an abnormal crack of a forging plate is presented in this work. The crack was found after forging process. Macro-analysis, SEM, composition inspection, metallographic analysis, inclusion analysis, EPMA and EDS were implemented. SEM shows that cleavage fracture is the main feature of the fracture surface, according to which it can be decided that the fracture is brittle fracture. XRF and carbon and sulphur analyzer indicate regular composition condition of the plate. EPMA and EDS suggest phosphorus segregation spread a lot around the crack. The results indicate that: brittleness caused by phosphorus segregation around crack zone is the main reason that cracks generate in the 12Cr13 steel during forging. As all we know, phosphorus has deleterious effect on toughness of steel because of its enrichment on grain boundaries, which can weaken the bond strength of grain boundary. Its existence should be avoided and microstructure of the steel should be homogeneous when good plasticity and toughness are wanted.